2014
DOI: 10.3389/fpls.2014.00087
|View full text |Cite
|
Sign up to set email alerts
|

Divergent functions of the Arabidopsis mitochondrial SCO proteins: HCC1 is essential for COX activity while HCC2 is involved in the UV-B stress response

Abstract: The two related putative cytochrome c oxidase (COX) assembly factors HCC1 and HCC2 from Arabidopsis thaliana are Homologs of the yeast Copper Chaperones Sco1p and Sco2p. The hcc1 null mutation was previously shown to be embryo lethal while the disruption of the HCC2 gene function had no obvious effect on plant development, but increased the expression of stress-responsive genes. Both HCC1 and HCC2 contain a thioredoxin domain, but only HCC1 carries a Cu-binding motif also found in Sco1p and Sco2p. In order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 62 publications
(117 reference statements)
2
35
0
Order By: Relevance
“…Gonz alez and coworkers have shown that AtSco1 (formerly Hcc1) is essential for CoxII function, while Hcc2, lacking metal binding residues, was not essential. Here we show that AtSco1 is a specific metallochaperone for CoxII, accounting for the impact of the deletion of the Sco gene in the plant phenotype [38,39].…”
Section: Discussionmentioning
confidence: 81%
“…Gonz alez and coworkers have shown that AtSco1 (formerly Hcc1) is essential for CoxII function, while Hcc2, lacking metal binding residues, was not essential. Here we show that AtSco1 is a specific metallochaperone for CoxII, accounting for the impact of the deletion of the Sco gene in the plant phenotype [38,39].…”
Section: Discussionmentioning
confidence: 81%
“…Plants that lack detectable Complex IV activity, obtained by cultivation of immature seeds, have severe phenotypic alterations (Dahan et al ., ), showing the importance of CYTc‐dependent respiration for post‐germinative development. In a similar way, homozygous mutants in the Complex IV assembly factor gene HCC1 rescued by expressing the HCC1 cDNA from the embryo‐specific ABI3 promoter do not grow beyond the seedling stage (Steinebrunner et al ., ). The importance of Complex I for post‐germinative growth was also shown using knockout mutants in the gene that encodes the NDUFV1 subunit, which lack detectable Complex I activity (Kühn et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The imaging procedure and settings are described in Steinebrunner et al . (). For co‐localization analyses, intensity‐scatter plots were generated with the ‘Coloc 2’ and ‘Colocalization Threshold’ plug‐ins of the Fiji software (Schindelin et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…Roots of transgenic seedlings (7 to 10 d old) containing the 35S::AtCOX17-1-mRFP construct in the mt-gk background selected on hygromycin were analysed using the Zeiss (Jena, Germany) confocal laser scanning microscope 780. The imaging procedure and settings are described in Steinebrunner et al (2014). For co-localization analyses, intensity-scatter plots were generated with the 'Coloc 2' and 'Colocalization Threshold' plug-ins of the Fiji software (Schindelin et al, 2012).…”
Section: Confocal Laser Scanning Microscopymentioning
confidence: 99%